STANDARDIZATION IN THE FIELD OF HOSPITALITY – THE NEED FOR MODERNITY AND THE FACTOR OF ATTRACTING FOREIGN INVESTMENTS - Yakovlieva-Melnyk, N. H.; Dzhyndzhoian, V. V. (Systems and Technologies, 2024)
The article is devoted to problems in the field of hospitality – competitiveness, investment attractiveness, which are associated with an insufficient level of sustainability, lack of guarantees and non-compliance with world-class standards. The authors of the study considered standardization and certification systems of various levels, which today are an integral part of the activities of hospitality market participants. The article presents the main trends of the hotel and restaurant business market: active recovery of demand for hospitality services, combination of work on vacation («leisure' stays»), hyperpersonalization of demand, health care, which require additional efforts and funds from industry participants. An indisputable confirmation of the quality of services and management at the enterprise is compliance with standards and norms, the indicators of which are aimed at achieving the goals of sustainable development, the enterprise, the industry, the region and the country as a whole. The article examines the features of the ESRS, IFRS S1 and IFRS S2 standards, a set of Hotel Sustainability Basics indicators, GSTC industry criteria, and ISO standards. Standards that have been working for several decades remain relevant. They control quality in various areas. New problems contribute to the creation of new standards. The IFRS S1 and IFRS S2 standards, which were released just last year, aim to keep companies on track to meet the Sustainable Development Goals. The standards are designed to create trust and confidence in the activities of enterprises, to help find a common language regarding the impact of climate risks between investors and businesses. The authors present the main problematic points of standardization processes for the Ukrainian hospitality market and further prospects for the development of the industry. It is emphasized that compliance with standards of different levels and directions by hospitality establishments not only provides guarantees to consumers when making a decision to purchase a service, but also acts as a guarantor of stability and perspective for investors who decide to invest in new hotel and restaurant business projects. Such steps will help the fastest recovery and sustainable development of domestic enterprises in the field of hospitality. Domestic enterprises will be able to confidently compete in the global hospitality market.